2014
DOI: 10.1186/s12876-014-0223-9
|View full text |Cite
|
Sign up to set email alerts
|

The EPIYA-ABCC motif pattern in CagA of Helicobacter pyloriis associated with peptic ulcer and gastric cancer in Mexican population

Abstract: BackgroundHelicobacter pylori chronic infection is associated with chronic gastritis, peptic ulcer, and gastric cancer. Cytotoxin-associated gene A (cagA)-positive H. pylori strains increase the risk of gastric pathology. The carcinogenic potential of CagA is linked to its polymorphic EPIYA motif variants. The goals of this study were to investigate the frequency of cagA-positive Helicobacter pylori in Mexican patients with gastric pathologies and to assess the association of cagA EPIYA motif patterns with pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
21
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 57 publications
9
21
1
4
Order By: Relevance
“…A significant association similar between peptic ulcer (54.5%) and CagA variants carrying 2 or more EPIYA C also was detected in Mexico, recently (Beltrán-Anaya et al, 2014). These data are consistent with other studies, and the presence of a larger number of CagA EPIYA-C segments is considered a risk factor for gastroduodenal ulceration (Panayotopoulou et al, 2010;Salih et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A significant association similar between peptic ulcer (54.5%) and CagA variants carrying 2 or more EPIYA C also was detected in Mexico, recently (Beltrán-Anaya et al, 2014). These data are consistent with other studies, and the presence of a larger number of CagA EPIYA-C segments is considered a risk factor for gastroduodenal ulceration (Panayotopoulou et al, 2010;Salih et al, 2010).…”
Section: Discussionsupporting
confidence: 87%
“…Thus, determining the CagA type found in each H. pylori infection may confer additional benefit to previously identify populations that have a higher risk of developing peptic ulcer and gastric cancer (Beltrán-Anaya et al, 2014;Huang et al, 2003). Therefore, the aim of Diagnostic Microbiology and Infectious Disease xxx (2015) xxx-xxx this study is to investigate whether the presence of CagA EPIYA variations in H. pylori is related to differing degrees of gastric mucosal disease in patients from south Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…These tyrosine phosphorylation domains are classified as EPIYA- A, B, C, or D, and differ between Western strains (containing A, B, and C domains) and East Asian strains (containing A, B, and D domains) 31 . The number and types of repeats have been associated with differing risks of carcinogenesis 58 . Recently, it was reported that the EPIYA-B motif binds and activates PI3-kinase and AKT, but many Western strains of H pylori carry a single nucleotide polymorphism in this domain that reduces its association with PI3 kinase and also reduces the risk of gastric cancer 59 .…”
Section: Virulence Factorsmentioning
confidence: 99%
“…Las diferencias en las manifestaciones clínicas y la gravedad de las enfermedades gástricas dependen de la virulencia de H. pylori, conferida especialmente por los genes cag A, vac A, dup A, ice A, oip A y bab A, los cuales se consideran predictores de resultados clínicos graves (39,40). El gen Vac A está asociado a la expresión de citotoxinas y su análisis estructural muestra dos regiones: la región señal (s) y la región media (m); a su vez, la primera está dividida en los subtipos s1a, s1b y s2, algunos de los cuales han sido asociados a enfermedades como úlcera péptica y cáncer gástrico.…”
Section: Resultados Y Discusiónunclassified
“…Los genes cag A, vac A, dup A, ice A, oip A y bab A han mostrado ser predictores de resultados clínicos graves (1,39,(42)(43)(44). La presencia del genotipo vac A-s1 se asocia con una mayor frecuencia de úlcera péptica, mientras que el genotipo cag A se asocia en su mayoría con gastritis crónica atrófica y adenocarcinoma gástrico (1,40,44,45). La relación de cag A con úlcera péptica puede ser manifestación de su expresión conjunta con el genotipo vacA-s1 (1,46).…”
Section: Resultados Y Discusiónunclassified